Strategi Rekrutmen dan Seleksi Karyawan Disabilitas di PT Sumber Alfaria Trijaya Tbk - Windarsih, Christiana; Wendra, Wendra (Journal of Emerging Business Management and Entrepreneurship Studies, 2024)
PT Sumber Alfaria Trijaya Tbk is committed to providing equal employment opportunities to people with disabilities. This research aims to develop a recruitment and selection strategy for employees with disabilities at Alfamart as an inclusive company. The research method is descriptive qualitative. Primary data sources were obtained through interviews with PT Sumber Alfaria Trijaya Tb management team who understand the business direction and human resource management strategy of the company. Meanwhile, secondary data was collected through document study. The research results show that the strategic direction of the PT Sumber Alfaria Trijaya Tb organization is to become an open inclusion company for people with disabilities. Therefore, human resource management strategy must be derived from organizational strategy in a series of human resource management activities, especially starting from employee recruitment and selection activities. This research proposes a draft strategy for recruitment and selection of employees with disabilities at PT Sumber Alfaria Trijaya Tbk as an inclusion company through implementing a buy and make strategy for employees with disabilities, as well as collaborating with foundations and schools for people with disabilities to include a retail learning curriculum as an effort to reach more potential employees, as well as improving methods for selecting disabled employees and developing the business technology-based selection process. Finally, this research also provides practical and academic suggestions.